2021
DOI: 10.36227/techrxiv.17169080.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Explainable AI and Random Forest Based Reliable Intrusion Detection system

Abstract: <p>Emerging Cyber threats with an increased dependency on vulnerable cyber-networks have jeopardized all stakeholders, making Intrusion Detection Systems (IDS) the essential network security requirement. Several IDS have been proposed in the past decade for preventing systems from cyber-attacks. Machine learning (ML) based IDS have shown remarkable performance on conventional cyber threats. However, the introduction of adversarial attacks in the cyber domain highlights the need to upgrade these IDS beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…At the local level, they use a Decision Plot to explain decisions on individual instances of the datasets. Another similar work is the framework proposed by [94], consisting of a Random Forest model using SHAP. The model can assess the credibility of the predicted results and ensure a high level of accuracy in detecting modern Cyber threats.…”
Section: ) Explainable Artificial Intelligence In Idssmentioning
confidence: 99%
“…At the local level, they use a Decision Plot to explain decisions on individual instances of the datasets. Another similar work is the framework proposed by [94], consisting of a Random Forest model using SHAP. The model can assess the credibility of the predicted results and ensure a high level of accuracy in detecting modern Cyber threats.…”
Section: ) Explainable Artificial Intelligence In Idssmentioning
confidence: 99%
“…Syed et al [213] suggested an Intrusion Detection System that used the global explanations created by the SHAP and Random Forest joint framework to detect all forms of malicious intrusion in network traffic. The suggested framework was composed of 2 stages of Random Forest classifiers and one SHAP stage.…”
Section: ) Network Intrusionmentioning
confidence: 99%
“…Anomaly detection. Khan et al [131] leveraged global explanation on Tree-SHAP to correlate an RF decision for explainable IDS. Their explainable IDS architecture comprised three main modules: (1) RF classifier (RFC) module for security predictions; (2) SHAP module extracting values relative to each feature of the dataset, and representing the importance of each feature in the decision made by the RFC; (3) Credibility assessment module (CAM), which utilizes the prediction and Shapley values to evaluate the confidence of prediction made by the RFC.…”
Section: Explanations For Improving the Performance Of Classifiersmentioning
confidence: 99%